Effectiveness of passive case detection for imported malaria in a hospital setting in Sri Lanka during the prevention of re-introduction phase of malaria. Issue 1 (22nd August 2018) - Dharmawardena, Priyani; Premaratne, Risintha; Mendis, Kamini; Wickemasinghe, Rajitha; Rodrigo, Chaturaka; Harintheran, Arungirinathan; Fernando, Deepika
Abstract: Introduction: The effectiveness of the passive case detection (PCD) system for imported malaria was assessed in government hospitals in Sri Lanka post-elimination of malaria. Methods: In 18 medical wards (test wards) in four government hospitals, the referral for malaria testing and the diagnosis of malaria by the ward physicians were monitored. Concurrently, in-ward febrile patients were assessed independently for their eligibility for referral for malaria diagnosis and were tested for malaria. The malaria incidence in 16 other wards (control wards), which the study did not screen, served as controls. Results: Four imported malaria patients were diagnosed within the PCD system among 25 874 febrile patients admitted during the 14-month study period, two of whom were diagnosed in the test wards and two in the control wards. The study's screening programme did not detect any more malaria patients than detected by the routine PCD system of the wards. However, far fewer patients were screened for malaria (1.3%) than were eligible for screening (29.4%), and some infections were detected incidentally, rather than by a request for a malaria test. Conclusion: A continuous effort to maintain awareness of the disease among physicians would be required if the PCD system is to be effective for the detection of imported malaria, post-elimination.